Analisis Dosis Radiasi Pada Kelenjar Tiroid Selama Pemeriksaan Dental Panoramik Di Instalasi Radiologi RSKDGM Provinsi Sulawesi Selatan - Darmawan, Zulkifli Tri; Pradana, Alfa; Mirfauddin, Mirfauddin (Jurnal Imejing Diagnostik (JImeD), 2025)
Background: The thyroid gland is highly sensitive to radiation and can easily be exposed during panoramic dental imaging. Although BAPETEN sets the annual public dose limit at 1 mSv, and ICRP 103 suggests a specific limit of 0.04 mGy per year for the thyroid, the use of personal protective equipment (PPE) is still often neglected in daily practice. This study aimed to assess how much radiation the thyroid receives during panoramic dental examinations without PPE.Methods: This study used a descriptive quantitative approach and was conducted at the Radiology Department of the Regional Dental and Oral Hospital, South Sulawesi. Ten patients undergoing panoramic radiography were selected. The thyroid radiation dose was calculated using five formulas: exposure dose, scatter dose, absorbed dose, equivalent dose, and effective dose. Technical factors such as tube voltage, current, exposure time, and distance to the thyroid were also recorded.Results: The absorbed dose to the thyroid gland obtained from 10 patients ranged from 0.0139 mGy to 0.0239 mGy, with a mean value of 0.0165 mGy and a standard deviation of 0.0035 mGy. These results indicate a relatively narrow distribution despite variations in patient body size and exposure parameters. All measured doses remained well below the annual organ dose limit of 0.04 mGy, as recommended by the International Commission on Radiological Protection (ICRP). However, existing literature has highlighted that even low-dose radiation exposures, when repeated and unshielded, may increase the stochastic risk of developing thyroid cancer—particularly in younger or genetically predisposed individuals. While the current findings confirm that radiation exposure during panoramic dental examinations is within acceptable limits, they also underscore the need for precautionary measures. The results support the practical implementation of the ALARA (As Low As Reasonably Achievable) principle, especially through the consistent use of thyroid shields during panoramic imaging, as a critical component of evidence-based radiation protection strategies.Conclusions: Panoramic dental imaging without thyroid shielding still produces radiation doses that are within acceptable limits. However, it is strongly recommended that PPE be used consistently, along with adherence to the ALARA principle, to ensure maximum patient safety.